ANALISIS PENERAPAN ACTIVITY BASED COSTING DALAM PENENTUAN TARIF JASA RAWAT INAP (STUDI KASUS PADA RUMAH SAKIT PUSRI PALEMBANG) - Husnul Urfah (AKUNTABILITAS, 2015)
The purpose of this research is to find out how the determination of inpatient tariff has been done by using activity based costing and to find out the great comparison of the inpatient tariff by using accounting based costing and the hospitalization rate used by the hospital. Quantitative method is used as the research method. The calculation of inpatient tariff which has been done by using ABC method has found the amount of room tariff for Super VIP class is Rp 1.094.112, VIP class is Rp 842.083, IA class is Rp 664.216, IB class is Rp 529.010, II class is Rp 466.070, and III class is Rp 369.983. Rate difference for class Super VIP Rp 94.112, class VIP Rp 42.083, class IA Rp 164.216, class IB Rp 129.010, class II Rp 226.070, dan class III Rp 219.983. Results of calculation of inpatient tariff by using activity-based costing method, when compared with the inpatient tariff used by the hospital at this time shows that for class II and III give the results are greater than other class because the imposition of overhead costs used ABC method for class II and III amount Rp 3.714.191.003 dan Rp 2.414.407.443, while the imposition of overhead costs by used tariff has been determined by hospital (tariff for class II Rp 240.000 and class III Rp 150.000) for class II and III amount Rp 1.912.600.000 and Rp 978.857.143. Because of that, the hospital should conduct an evaluation for the imposition overhead costs with reducing the cost of existing activities such as electricity cost, water and facilities depreciation.